Field evaluation of botanical and synthetic insecticides against fall armyworm in maize - HAMDAN MARULI SIREGAR; DADANG DADANG; DEWI SARTIAMI; I WAYAN WINASA; ELI ZULKATRI (Society for Indonesian Biodiversity, 2025)
Abstract. Siregar HM, Dadang, Sartiami D, Winasa IW, Zulkatri E. 2025. Field evaluation of botanical and synthetic insecticides against fall armyworm in maize. Biodiversitas 26: 5125-5131. Fall armyworm (Spodoptera frugiperda) has emerged as a significant threat to maize production in Indonesia, leading to significant yield losses and ecological risks in control practices due to the overreliance on synthetic insecticides. This study aimed to evaluate the effects of botanical and synthetic insecticide applications on the population abundance and attack intensity of S. frugiperda, as well as their impact on parasitoid parasitism rate. The field experiment was conducted at the Sawah Baru Experimental Farm, IPB University, during the vegetative stage using a Randomized Block Design (RBD) with seven blocks and three treatments. These treatments include a botanical insecticide formulated as a 50 Emulsifiable Concentrate (EC) from a hexane extract mixture of Piper retrofractum fruits and Annona squamosa seeds (2:1 w/w), a synthetic insecticide (emamectin benzoate 30 EC), and a control. The data was analyzed using the Kruskal-Wallis test and Structural Equation Modeling (SEM) in R Studio version 4.4.2. The results showed that both insecticides effectively reduced the population abundance and attack intensity of S. frugiperda, with the synthetic insecticide exhibiting higher efficacy. However, the botanical insecticide was found to be relatively safer for parasitoids. These findings emphasize the potential of botanical insecticides as a promising and ecologically safer alternative for pest control, suitable for integration into Integrated Pest Management (IPM) strategies, thereby supporting a more sustainable approach to maize production.